Study of Correlation Between Glycated Hemoglobin (Hba1c) and Serum Lipid Profile in Type 2 Diabetic Patients - Shrestha, Anil (Journal of Nepalgunj Medical College, 2020)
Introduction: Diabetic mellitus is a chronic metabolic disease characterized by hyperglycemia. Type 2 diabetes mellitus accounts for more than 90% of cases worldwide. Elevated HbA1c and dyslipidemia proportionately increases the risk of development of cardiovascular disease (CVD) which is the major cause of morbidity and mortality worldwide. Aims: To Study the correlation between glycated hemoglobin (HbA1c) and serum lipid profile in type 2 diabetic patients. Methods: This is a hospital based cross sectional study conducted at Nepalgunj medical college teaching hospital, which included 104 type 2 diabetic patients (54 males and 50 females).Venous blood samples were collected from all patients and serum was used for analyzing HbA1c, lipid profile panel and fasting blood glucose (FBG). DM was defined as per American diabetic association (ADA) criteria. Dyslipidemia was defined as per the National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III Guidelines. The data were analyzed using standard statistical methods, including SPSS 21. Results : Abnormal lipid parameters were demonstrated with increased Total Chloseterol (TC), Triglyceride (TG), Low density lipoprotein (LDL),Very low density lipoprotein (VLDL) and low High density lipoprotein (HDL) suggestive of dyslipidemia.HbA1c showed direct and significant correlation with TC,LDL,TG and VLDL. Patients with HbA1c > 7.0% had a significantly higher value of TC, LDL, TG and VLDL as compared to patients with HbA1c ≤7.0%.However, the significant difference in value of HDL-C was not found between two groups. Conclusion: Due to the strong correlation with lipid profile, HbA1c could be the ideal marker for predicting dyslipidemia in type 2 DM . Patients with higher HbA1c value and dyslipidemia should be considered as a very high risk group for CVD.